24 Jie Ling Gu (24 Festive Drums): Imagining the 24 Jie Ling (Phenomena) of China in Enacting Cultural Solidarity among the Chinese Diaspora of Malaysia - Chan, Clare Suet Ching (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
The 24 Jie Ling Gu (24 Festive Drums) is a drum ensemble that consists of 24 lion drums (shigu) played by twenty-four drummers who move to spectacular and dynamic choreography in synchronization with the rhythmic patterns struck on the shigu. It is an “invented tradition” created by the Chinese diaspora of Malaysia. In response to the 1970s National Cultural Policy (NCP) which aimed toward the construction of a homogenized national identity, the Chinese founded the 24 Jie Ling Gu ensemble to enact cultural solidarity and unify the people toward a sense of belonging to their distant motherland in China. They created the music and movements of the 24 Jie Ling Gu to manifest the 24 jie ling (phenomena)—the weather changes, agricultural activities, and natural phenomenon inherent in the 24 jie qi (jie: joints; qi: breath) or seasonal periods. Due to the fact that the Chinese of Malaysia have not physically experienced China but are connected to it through literature and media technology, I argue that the 24 Jie Ling Gu performers utilized their imagination and localized experience of Malaysia to manifest the 24 jie ling in China. This article is based on ethnographic fieldwork and ongoing revisits to this genre through a span of more than 20 years.